Exoticisms and Barbarisms in Biographical Novel Translation (Case Study of D. Goodwin’s "Diva") - Chernikova, Oleksandra (Studia Philologica, 2025)
The article is focused on rendering exoticisms and barbarisms in the translation of a biographical novel, namely Diva by Daisy Goodwin (translated by the author of this article). The research material contains numerous exoticisms and barbarisms used in the novel to create an atmosphere of ‘otherness’, to symbolize the sophisticated life of a diva, as well as her life’s work at the opera and her more ‘human’ side: love, temptation etc. Due to the original containing multiple borrowed words to create such symbolism, it has been logical for the translator to use a similar strategy in their rendering: both exoticisms and barbarisms remain alien and otherworldly, however, to avoid overwhelming the reader with the abundance of foreign vocabulary, the translator adds description or (mostly) commentary.